Modern Manors: Welfare Capitalism Since the New Deal - Taras, Daphne Gottlieb (Relations industrielles / Industrial Relations, 1998)
The article reviews the book, "Modern Manors: Welfare Capitalism Since the New Deal," by Sanford M. Jacoby.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Employment practices; History; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Welfare